Penerapan Metode Pengajaran Project Based Learning (PjBL) Terhadap Model Pembelajaran Bahasa Indonesia - Hasna Salsabila; Hindun Hindun (Lembaga Pengembangan Kinerja Dosen, 2024)
The teaching methods that educators can apply in teaching and learning activities are very varied, the aim is so that students do not get bored quickly and can increase activity in class. One teaching method that can be used is project based learning or abbreviated as PjBL, this method is project based which can increase students' critical and active thinking when learning activities take place. The research used a literature review method using 15 articles which aimed to examine how successful the project based learning teaching method was used for learning Indonesian. Based on the results of data analysis and reviewing 15 articles, it can be concluded that the application of the project based learning teaching method for learning Indonesian was successful and had a very positive impact on students when teaching and learning activities took place.